Relações sociais e autopercepção da saúde em idosos: Projeto Envelhecimento e Saúde - Ana Paula Nogueira Nunes (2011)
OBJECTIVE: To investigate the association between social relationships and self-perceived health in older adults. METHODS: This was a cross- sectional study of a representative sample of elderly covered by the Family Health Program and residents in an area of high vulnerability to health in Belo Horizonte, MG. Information was obtained through structured interviews. Factors associated with bad or very bad self perceived health were identified by multiple logistic regression analysis. RESULTS: 363 out of 371 eligible elderly participated. 17.1% of elderly self-perceived their health as bad. There was a positive dose response relationship between bad self- perceived and the number of chronic diseases and the degree of difficulty to perform the activities of daily living. Elderly who perceived their personal relationships as bad and who could not count on anyone if necessary to stay in bed were more likely to self-perceive their health as poor. Working out was negatively associated with self-perceived poor health. CONCLUSION: The results confirm the multidimensional structure of self-perceived health including the issues related to health and social relationships. They strengthen the role of social relations on health.